Systemic Metal Ion Concentrations in Patients With Hip and Knee Megaprostheses: A Prospective Cohort Study - Kiki Q. de Smidt, BSc; Geert Spierenburg, MD; Richard E. Evenhuis, MD; Sarah E. Bosma, MD, PhD; Robert J.P. van der Wal, MD, PhD; Demien Broekhuis, MD; Michiel A.J. van de Sande, MD, PhD (Arthroplasty Today, 2022)
Background: Local tissue and serum metal ions have been shown to be elevated in some metal-on-metal and metal-on-polyethylene joint replacements. Local elevations have been linked to adverse local tissue reactions in some patients, and systemic elevation has been less commonly implicated cardiac and neurologic issues. Using a prospective study design, we aimed to identify the changes in serum metal ion levels after hip or knee megaprosthesis reconstruction. Furthermore, we will evaluate the occurrence of adverse effects and complications, possibly linked to metal ion elevation. Methods: Fourteen consecutive patients receiving a Modular Universal Tumor Revision System megaprosthesis were enrolled. Blood samples were collected preoperatively and postoperatively to determine the serum ion concentrations of aluminum, chromium, cobalt, and silver. To evaluate the safety of the megaprostheses and the subsequently possible related (elevated) serum metal ion concentrations, all adverse effects and complications were registered until last outpatient clinic visit at the time of this study. Results: Compared to the preoperative median serum concentrations, the postoperative median serum concentrations of chromium, silver, and cobalt increased 11-fold, 62-fold, and 64-fold, respectively. The median serum concentration of aluminum increased with 16%. Elevations were primarily noted in patients with knee prostheses. Eight patients had no adverse effects or complications during the period between preoperative and postoperative blood sampling. One adverse effect directly related to the serum metal ion concentrations, namely argyria, was observed. Conclusions: This study documents significantly elevated concentrations of the metal ions, but only one adverse effect directly related to the metal ion concentrations was observed. Future studies are needed to further assess the impact of elevated metal ion levels after megaprostheses, specifically knee implants, which are metal-on-metal.